2014
DOI: 10.3393/ac.2014.30.5.228
|View full text |Cite
|
Sign up to set email alerts
|

Prompt Management Is Most Important for Colonic Perforation After Colonoscopy

Abstract: PurposeThe incidence of complications after colonoscopy is very low. The complications after colonoscopy that are of clinical concern are bleeding and perforation. The present study was conducted to determine the clinical outcomes and the risk factors of a colostomy or a colectomy after colonoscopic colon perforation.MethodsFrom March 2009 to December 2012, the records of all patients who were treated for colorectal perforation after colonoscopy were reviewed retrospectively. The following parameters were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…These findings are similar to previous studies, with Iqbal et al identifying patients presenting at >24 h were more likely to have gross contamination and require faecal diversion . Time to diagnosis thus influences the operative management, as well as hospital LOS …”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to previous studies, with Iqbal et al identifying patients presenting at >24 h were more likely to have gross contamination and require faecal diversion . Time to diagnosis thus influences the operative management, as well as hospital LOS …”
Section: Discussionsupporting
confidence: 90%
“…Perforation was diagnosed in a third dog by thoracic radiography that included the cranial abdomen. Ultrasonography In several studies, morbidity rate increased in people when perforations were diagnosed >24 hours after endoscopy, 16,31,34 but other studies found no association between the time to detection and patient prognosis. 14,17 The low number of cases in our series limits the ability to determine risk factors, but morbidity was higher in animals with delayed diagnoses.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Such patients need prompt evaluation for a colon perforation. 20 Abdominal plain films are diagnostic in most cases if they depict extraluminal free air. Computed tomography scans may be needed in patients with negative or equivocal radiographs.…”
Section: Diagnosismentioning
confidence: 99%
“…Early diagnosis and appropriate management mitigate the morbidity and the mortality associated with colonoscopic perforation. 20 However, the lack of large prospective randomized trials and specific guidelines makes it difficult to define optimal management of colonoscopic perforations. 23 In stable patients, treatment options range from nonoperative management to laparotomy with colon resection.…”
Section: Managementmentioning
confidence: 99%